1992
DOI: 10.1017/s0043174500051808
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, Translocation, and Metabolism of Clomazone, Metribuzin and Linuron in Soybean (Glycine max) and Common Cocklebur (Xanthium strumarium)

Abstract: Research was conducted in soybean and common cocklebur to determine if the synergistic interactions of clomazone plus metribuzin and clomazone plus linuron were due to the effect of one herbicide on root uptake, partitioning, or metabolism of the other. Treatments consisted of14C-clomazone alone and combined with metribuzin or linuron,14C-metribuzin alone and combined with clomazone, and14C-linuron alone and combined with clomazone. Root uptake and partitioning of clomazone applied alone in soybean differed co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…Differential absorption, translocation, or metabolism does not adequately explain differences in selectivity among species (Liebl and Norman 1991;Scott and Weston 1992;Weimer et al 1992;Weston and Barrett 1989). Several researchers have speculated that different sites of action or differences in the sensitivity of a common site of action may be responsible for differential tolerance among species (Norman et al 1990a;Salzman et al 1992;Weimer et al 1992;Weston and Barrett 1989).…”
mentioning
confidence: 99%
“…Differential absorption, translocation, or metabolism does not adequately explain differences in selectivity among species (Liebl and Norman 1991;Scott and Weston 1992;Weimer et al 1992;Weston and Barrett 1989). Several researchers have speculated that different sites of action or differences in the sensitivity of a common site of action may be responsible for differential tolerance among species (Norman et al 1990a;Salzman et al 1992;Weimer et al 1992;Weston and Barrett 1989).…”
mentioning
confidence: 99%
“…A previous study reported that rapid metabolism of mesotrione confers mesotrione resistance in atrazine‐ and HPPD inhibitor‐resistant Palmer amaranth from Nebraska (Nakka et al, 2017a), and rapid metabolism of atrazine confers atrazine resistance in this biotype (Chahal et al, 2019). A study conducted by Salzman et al (1992) reported that clomazone {2‐[(2‐chlorophenyl) methyl]‐4, 4‐dimethyl‐3‐isoxazolidinone}, belonging to same mode‐of‐action as mesotrione, reduced metabolism of metribuzin [4‐amino‐6‐(1,1‐dimethyethyl)‐3‐(methylthio)‐1,2,4‐triazin‐5 (4H)‐one] or linuron [3‐(3,4‐dichorophenyl)‐1‐methoxy‐1‐methylurea] (PS II inhibitor) in common cocklebur ( Xanthium strumarium L.) when tank mixed, thus providing greater control compared to metribuzin or linuron applied alone. Atrazine metabolism was not affected when mesotrione was included in tank mixture compared with atrazine applied alone; however, information on mesotrione metabolism when tank mixed with atrazine is not available.…”
Section: Discussionmentioning
confidence: 99%
“…While Palmer amaranth in Nebraska has been confirmed resistant to both atrazine and HPPD inhibitors, synergistic interaction was observed with their tank mixture applied POST (Jhala et al, 2014). Besides the biochemical and physiological overlap of atrazine and mesotrione due to their complementary site of action when applied in a tank mixture (Hess, 2000; Pallett et al, 1998), mechanism of synergism might also involve other biochemical and physiological effects including increased herbicide uptake or translocation, reduced herbicide detoxification, and/or increased susceptibility of different plant parts to a herbicide action (Putnam and Ries, 1967; Salzman et al, 1992; Shaw and Wesley, 1993), resulting in improved control of atrazine‐ and HPPD inhibitor‐resistant Palmer amaranth. Therefore, the main objectives of this study were to (i) determine the response of atrazine‐ and HPPD inhibitor‐resistant Palmer amaranth to different rates of mesotrione or atrazine applied POST alone or in tank mixture, (ii) quantify the absorption and translocation of 14 C‐atrazine or 14 C‐mesotrione applied alone or tank mixed with commercial formulations of mesotrione or atrazine, respectively, and (iii) determine the metabolism of 14 C‐atrazine applied alone or tank mixed with a commercial formulation of mesotrione in atrazine‐ and HPPD inhibitor‐resistant and susceptible Palmer amaranth from Nebraska.…”
mentioning
confidence: 99%
“…Compared with longgrain cultivars, medium grain cultivars were less tolerant to clomazone. Several researchers have speculated that different sites of action or differences in the sensitivity of a clomazone site of action may be responsible for differential tolerance among species (Norman et al 1990a;Salzman et al 1992;Weimer et al 1992;Weston and Barrett 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Hydroponic techniques rapidly screen cultivar tolerance by using shoot and root biomass reductions, along with visual injury symptoms (Newsom and Shaw 1992). Salzman et al (1992) grew soybean plants in a nutrient solution to determine the effects of clomazone plus metribuzin or clomazone plus linuron on root uptake, partitioning, and metabolism. Root uptake and partitioning of clomazone in soybean differed compared with clomazone plus metribuzin.…”
Section: Introductionmentioning
confidence: 99%